Soil Degradation in North - Eastern hill Region of India - an overview - , Patiram; Bhaduria, S. B. S. (Indian Forester, 1995)
In the North-Eastern Hill region of India, shifting cultivation (Jhum), deforestation, faulty method of cultivation on hill slopes and construction of road etc. are the major cause of soil degradation. The soil acidity, deficiencies of bases and phosphorus limit the productivity of crops to a great extent. It is unrealistic to prohibit the cultivation of all hill slopes on which farmers depend for their livelihood. Therefore, some socially, economically and environmentally acceptable methods for sustained production are suggested. The existing traditionally good practices in few pockets of the region sustaining productivity without soil degradation also need careful studies to extend them to other agroclimatic zones. A system approach involving integrated attention to agroforestry including crop and livestock farming may be helpful in preserving the soil health.